2014
DOI: 10.1080/02614367.2014.966744
|View full text |Cite
|
Sign up to set email alerts
|

Music, dancing and clothing as belonging and freedom among people seeking asylum in the UK

Abstract: This article explores how dancing, music and clothing provide vital modes of identification and freedom in the lives of people seeking asylum in the UK which are otherwise ostensibly marked by lack of choice. People who make a claim for asylum are accommodated in towns and cities around the UK under a compulsory dispersal system. The rapid emergence of new music leisure spaces demonstrates the importance of music and dancing for processes of settlement and negotiation of belonging. Music and 'community' events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
2
26
0
5
Order By: Relevance
“…For example, a study on Chinese migrants' social dance in Japan showed that "dance was obviously used as a shelter and social haven by the participants" (Liu-Farrer, 2004, p. 668). Socializing can act as a refuge from social isolation and boredom (Lewis, 2015), and migrants can benefit from interactions with locals to create feelings of acceptance (Putnam, 2000). Peperkamp (2018) stressed that "even superficial interactions may be important in this regard" (p. 258).…”
Section: Leisure Migration and Quality Of Lifementioning
confidence: 99%
“…For example, a study on Chinese migrants' social dance in Japan showed that "dance was obviously used as a shelter and social haven by the participants" (Liu-Farrer, 2004, p. 668). Socializing can act as a refuge from social isolation and boredom (Lewis, 2015), and migrants can benefit from interactions with locals to create feelings of acceptance (Putnam, 2000). Peperkamp (2018) stressed that "even superficial interactions may be important in this regard" (p. 258).…”
Section: Leisure Migration and Quality Of Lifementioning
confidence: 99%
“…At the same time, there are several accounts of the positive contributions leisure can make to refugee resettlement. Leisure can serve important social functions, such as expanding social networks and bonds, improving social cohesion and nurturing deep cultural meanings [14,15]. Given the mobile existence experienced by refugees, the creation of connections to other individuals, to place and to the new culture in which they have resettled seems urgent and necessary for the establishment of a sense of belonging [16] as well as to supporting a positive sense of wellbeing [17].…”
Section: Leisure Meaningsmentioning
confidence: 99%
“…Through leisure, migrant people can gain social support, expand their networks, develop their sense of place and alleviate so-called settlement distress (Hasmi, Gross and Scott-Young 2014;Kim and Scott 2000;Stodolska 2002;Tirone and Pedlar 2000). 'Going out' and socialising can act as a refuge from the conditions of social isolation and boredom in which many find themselves (Lewis 2015). The meaningfulness of leisure also involves processes of self-realisation and self-expression, and this can enable a sense of self in a world of flux and uncertainty (Mata-Codesal, Peperkamp and Tiesler 2015).…”
Section: Leisure and Migrationmentioning
confidence: 99%
“…It permitted participants to connect with former ways of life, which can help to preserve cultural identities (Kim et al 2002;Stodolska 2002). Clothing, music, singing and games/play also appeared as significant ways to demonstrate and share culture, heritage and notions of belonging (Lewis 2015).…”
Section: Researchermentioning
confidence: 99%